Muscular Systems and Their Influence on Foot Arches and Toes Alignment—Towards the Proper Diagnosis and Treatment of Hallux Valgus - Dygut, Jacek; Piwowar, Monika (Diagnostics (Basel), 2022)
(1) Background: Static foot deformities, including hallux valgus, are common deformities. The subject under consideration is the role of extrinsic and intrinsic muscles working within muscular systems that shape the arches of the foot and the alignment of the toes. (2) Methods: Based on a literature review, the muscle systems were analyzed. The systems under consideration were as follows: “tendon stirrup” (system I); muscles complementary to the tendon stirrup (system II); “foot lever” (system III); muscles complementary to system III (system IV); “reins of hallux” (system V), a muscular system having distal inserts on the hallux. The shape of the foot arches was analyzed in this context. (3) Results: The correct arch architecture of the foot stabilized mainly by the extrinsic muscle systems determining the function of the intrinsic muscle systems of the foot is described. The proper function of muscular systems shaping the arches of the foot is a prerequisite for the proper function of muscles directly responsible for the alignment of the big toe (hallux) and other foot toes. (4) Conclusion: The action of muscles should be considered in groups (systems) because the action of the group of muscles results in the creation of a new quality of movement. The analysis of individual muscle-pulling forces, especially the moments of force in the weight-bearing foot, may lead to extremely incorrect conclusions. In pathological cases, the restoration of the correct arches of the foot guarantees the recovery of the correct function of the pulling forces of the foot muscles responsible for the physiological alignment of the hallux. This is especially important concerning conservative and surgical treatment of hallux valgus.